STUDI KRITIS TERHADAP TEORI IDENTITAS PIKIRAN-OTAK MARIO BUNGE: PERSPEKTIF NEO-SADRIAN - Cipta Bakti Gama (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2014)
The aim of this research is to conduct a critical analysis of Mario Bunge’s view that mental reality is identical with the reality of brain function known as mind-brain identity theory. The analysis is performed using Neosadrian perspective, i.e. a new form of Mulla Sadra’s philosophy which is developed by Tabataba‘i and his disciples. The author tries to elucidate the main claims held by Bunge and to launch some critiques upon those claims. The main conclusions achieved through this research include the following. Firstly, mind-brain identity theory cannot be accepted. Secondly, current development of scientific studies corroborating certain relations between brain and mental states does not justify the validity of the identity theory, also does not falsify its opposition. Thirdly, a religious-sufistical philosophy, such the Neosadrian, can be consistent with current development of scientific research.